American studies journal.
American Studies encourages interdisciplinary and transdisciplinary scholarship in U.S. cultures and histories broadly defined; frameworks of comparative, international, and/or transnational perspectives. With an editorial staff from a number of areas of study, the journal offers provocative perspectives on a variety of issues. Frequent special sections and special issues create a space for a broad discussion on a single topic. Articles on pedagogy inform the American Studies classroom. The book review section aims at keeping readers conversant with contemporary scholarship.